Mellan privilegium och sårbarhet: Fluktuerande känsloekonomier i Negar Nasehs De fördrivna - Arping, Åsa (Tidskrift för litteraturvetenskap, 2020)
How does it feel to be a part of today’s Swedish post-welfare society, where many people’s situation is utterly privileged yet at the same time emotionally precarious, and how are these conflicting experiences treated in contemporary fiction? These questions are in this article processed through Negar Naseh’s novel De fördrivna (2017), with particular focus on interrelations between gender, affect, and agency. The novel revolves around the upper middle-class couple Miriam and Filip, who together with their baby girl have left Stockholm for a villa in the Sicilian countryside – secluded, yet not far from the Mediterranean stream of refugees. The article pays special attention to Miriam’s ”change” in the story, from an initial distancing, to a burning commitment to the problem of migration. Based on Sianne Ngai’s concept ugly feelings and Sven Anders Johansson’s thoughts on today’s cynical condition, different possible interpretations of Miriam’s ”transition” and the novel’s brutal ending is discussed.